2012
DOI: 10.1590/s1678-77572012000100003
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitative treatment of cleft lip and palate: experience of the Hospital for Rehabilitation of Craniofacial Anomalies/USP (HRAC/USP) - Part 1: overall aspects

Abstract: Cleft lip and palate is the most common among craniofacial malformations and causes several esthetic and functional implications that require rehabilitation. This paper aims to generally describe the several aspects related to this complex pathology and the treatment protocol used by the Hospital for Rehabilitation of Craniofacial Anomalies, University of São Paulo (HRAC-USP) along 40 years of experience in the treatment of individuals with cleft lip and palate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
143
0
105

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(253 citation statements)
references
References 21 publications
5
143
0
105
Order By: Relevance
“…Cleft lip and palate is considered the most common craniofacial malformations that affect the lip, the alveolar ridge and/or palate, and when untreated, results in aesthetic, functional and psychosocial impairment, besides affecting social interactions (1) . This malformation originates between the 4 th and 12 th week of gestation, has a multifactorial etiology and is associated with genetic and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cleft lip and palate is considered the most common craniofacial malformations that affect the lip, the alveolar ridge and/or palate, and when untreated, results in aesthetic, functional and psychosocial impairment, besides affecting social interactions (1) . This malformation originates between the 4 th and 12 th week of gestation, has a multifactorial etiology and is associated with genetic and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…This malformation originates between the 4 th and 12 th week of gestation, has a multifactorial etiology and is associated with genetic and environmental factors. In Brazil, the prevalence is 1 per 650 births (1) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(17) Protocol stratification has been identified as an important quality indicator for the rehabilitation process of patients with cleft lip and palate, a fact that is evidenced in this study, related to surgery, demonstrating compliance to this recommendation. (2) Regarding nursing care after cheiloplasty and palatoplasty surgeries, it became clear that both groups were similar concerning correct answers in the pre-training; after training, greater knowledge was evidenced, denoting that they were able to hold information. (23) However, in the group receiving the intervention through the educational video, it was observed that learning was significantly higher, reflecting its importance as a training tool.…”
Section: Discussionmentioning
confidence: 99%
“…(1,2) The rehabilitation process of patients with cleft lip and palate begins with the primary plastic surgeries named cheiloplasty and palatoplasty, which are performed in the first months and years of life, respectively. Cheiloplasty is the reconstructive surgery of the cleft lip, and palatoplasty is the reconstruction of the cleft palate.…”
Section: Introductionmentioning
confidence: 99%